1976
DOI: 10.1152/jappl.1976.41.6.859
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function changes in ozone-interaction of concentration and ventilation

Abstract: A total of 28 healthy young subjects have been exposed for 2 h to ozone (0.37-0.75 ppm) under conditions of either rest or intermittent light exercise (sufficient to increase the respiratory minute volume by a factor of 2.5). All pulmonary function tests (vital capacity, forced expiratory volume, maximum expiratory flow-volume curve, slope of phase III of alveolar nitrogen plateau) showed a significant deterioration relative to parallel control experiments. Responses were related to the dose of ozone as calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(47 citation statements)
references
References 0 publications
5
41
0
1
Order By: Relevance
“…Exercise is expected to be an important modifier of the toxic effects of inhaled pollutant compounds, and a number of investigations have shown that exercise exposure to pollutant compounds exacerbates induced changes in pulmonary function of humans (Silverman et al, 1976;DeLucia and Adams, 1977;Adams et al, 1981). With the development of exercising animal models, inhalation toxicologic studies may address questions that cannot be approached with human subjects, such as exercise effects on histopathologic and biochemical changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Exercise is expected to be an important modifier of the toxic effects of inhaled pollutant compounds, and a number of investigations have shown that exercise exposure to pollutant compounds exacerbates induced changes in pulmonary function of humans (Silverman et al, 1976;DeLucia and Adams, 1977;Adams et al, 1981). With the development of exercising animal models, inhalation toxicologic studies may address questions that cannot be approached with human subjects, such as exercise effects on histopathologic and biochemical changes.…”
Section: Discussionmentioning
confidence: 99%
“…The dose rate of an inhaled pollutant is elevated by exercise due to increased respiratory ventilation; however, toxic effects may be further enhanced during exercise ventilation because of deeper penetration and redistribution of inhaled compounds in lung tissues (Silverman et al, 1976;DeLucia and Adams, 1977). Ozone is a prominent component of photochemical air pollution, and its toxic properties are well documented.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From this observation it can be reasonably extrapolated that similar damage occurs in the lungs of young children living in the same area. Since children tend also to be relatively active, any effects of air pollution would likely be amplified (Silverman et al, 1976;Mautzetal., 1985).…”
Section: Discussionmentioning
confidence: 99%